9:41 PM Fri 18 Sep
14.
Factorize the following:
8(x + 1)2 + 2 (x+1) – 15
Answers
Answered by
0
Answer:
Step-by-step explanation:
Given Equation is 12(x^2 + 7x)^2 - 8(x^2 + 7x)(2x - 1) - 15(2x - 1)^2
= > 12(x^4 + 49x^2 + 14x^3) - 8(2x^3 + 13x^2 - 7x) - 15(4x^2 + 1 - 4x)
= > 12x^4 + 588x^2 + 168x^3 - 16x^3 - 104x^2 + 56x - 60x^2 + 60x - 15
= > 12x^4 + 152x^3 + 424x^2 + 116x - 15
= > 12x^4 + 104x^3 + 48x^3 - 10x^2 + 416x^2 + 18x^2 - 40x + 156x - 15
= > 2x^2(6x^2 + 52x - 5) + 8x(6x^2 + 52x - 5) + 3(6x^2 + 52x - 5)
= > (2x^2 + 8x + 3)(6x^2 + 52x - 5).
Answered by
1
Answer:
8(2x+2) +2 (x+1) -15
16x+16+ (2x+2) -15
16x+16+2x+2-15
18x+18-15
18x+3
Hope it helps! Please mark it as brainliest if you want!
Similar questions